Acceptability of forage legumes for improved fallows - first experiences of agro-pastoralists in subhumid southwest Nigeria - Muhr, L.; Tarawali, Shirley A.; Peters, Michael; Schultze-Kraft, Rainer (Cambridge University Press, 2001)
In the process of developing an improved fallow system based on forage legumes, the potential interest of crop-livestock farmers in enhancing soil fertility restoration and dry-season feed supply was assessed during a socio-economic study on 11 farms of settled agro-pastoralists in the subhumid zone of West Africa. Simultaneously, eight farmers in the group participated in simple and largely farmer-managed on-farm experiments testing the establishment of selected forage legumes on fallow land. In addition to agronomic parameters, the participatory approach included an evaluation of the technology by farmers both during farm visits and field days. With cropping and dry-season feeding strategies increasingly being limited by land availability, the agronomic performance of some of the tested legume species, in particular Stylosanthes guianensis, promised substantial productivity gains once they could be integrated into the traditional fallow system. The major concerns of the farmers were animal health and labour supply for cropping activities, rather than soil fertility and feed constraints. The need for initial weed control within most of the legume species, therefore, limited their acceptability by farmers at this early stage of innovation testing. Nevertheless, farmers' interest grew remarkably in the course of the study. Options for the selection of appropriate species and management practices, which aimed at facilitating the establishment of legumes on fallow land, are discussed as a means of enhancing further adoption of the innovation.